Effects of Greenhouse Gas Increase and Stratospheric Ozone Depletion on Stratospheric Mean Age of Air in 1960–2010. Issue 4 (23rd February 2018) - Li, Feng; Newman, Paul; Pawson, Steven; Perlwitz, Judith
Abstract: The relative impacts of greenhouse gas (GHG) increase and stratospheric ozone depletion on stratospheric mean age of air in the 1960–2010 period are quantified using the Goddard Earth Observing System Chemistry‐Climate Model. The experiment compares controlled simulations using a coupled atmosphere‐ocean version of the Goddard Earth Observing System Chemistry‐Climate Model, in which either GHGs or ozone depleting substances, or both factors evolve over time. The model results show that GHGs and ozone depleting substances have about equal contributions to the simulated mean age decrease, but GHG increases account for about two thirds of the enhanced strength of the lower stratospheric residual circulation. It is also found that both the acceleration of the diabatic circulation and the decrease of the mean age difference between downwelling and upwelling regions are mainly caused by GHG forcing. The results show that ozone depletion causes an increase in the mean age of air in the Antarctic summer lower stratosphere through two processes: (1) a seasonal delay in the Antarctic polar vortex breakup that inhibits young midlatitude air from mixing with the older air inside the vortex, and (2) enhanced Antarctic downwelling that brings older air from middle and upper stratosphere into the lower stratosphere. Key Points: Greenhouse gas increases and stratospheric ozone depletion contribute nearly equally to the simulated mean age decrease in 1960–2010 Stratospheric ozone depletion causes an increase in mean age in the Antarctic summer lower stratosphere The relative impacts of greenhouse gases and stratospheric ozone on trends of mean age and the residual circulations are different